2014
DOI: 10.1007/s00439-014-1513-6
|View full text |Cite
|
Sign up to set email alerts
|

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes

Abstract: Copy number variation has emerged as an important cause of phenotypic variation, particularly in relation to some complex disorders. Autism spectrum disorder (ASD) is one such disorder, in which evidence is emerging for an etiological role for some rare penetrant de novo and rare inherited copy number variants (CNVs). De novo variation, however, does not always explain the familial nature of ASD, leaving a gap in our knowledge concerning the heritable genetic causes of this disorder. Extended pedigrees, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Family-based association studies in families with at least two affected males have shown that over-transmission of a DRD1 haplotype occurs from mother-to-son and genotype-phenotype assessments revealed significant associations with DRD1 polymorphisms (Hettinger et al, 2008). However, GWAS from ASD patients have mostly failed to identify candidate causative genes (Chaste et al, 2015;Woodbury-Smith et al, 2015), thereby warranting further studies to identify novel targets underlying the male bias in ASD.…”
Section: Autism Spectrum Disordersmentioning
confidence: 92%
“…Family-based association studies in families with at least two affected males have shown that over-transmission of a DRD1 haplotype occurs from mother-to-son and genotype-phenotype assessments revealed significant associations with DRD1 polymorphisms (Hettinger et al, 2008). However, GWAS from ASD patients have mostly failed to identify candidate causative genes (Chaste et al, 2015;Woodbury-Smith et al, 2015), thereby warranting further studies to identify novel targets underlying the male bias in ASD.…”
Section: Autism Spectrum Disordersmentioning
confidence: 92%
“…Similarly, Bernier et al (2012) reported that in families where more than one family member was diagnosed with ASD, more undiagnosed family members expressed BAP symptoms. Woodbury-Smith et al (2015) looked for a genetic link between parents' BAP and presence of specific CNVs in their children diagnosed with ASD, but could only find, Ba small number of CNVs transmitted from BAP parents to ASD offspring^(p. 196).…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
“…For example, four candidate ASD genes were identified in seven ASD/BAP pedigrees with ≥3 affected individuals 43 . Larger multiplex families remain scarce in the literature 20,44 . Here, we identified more subtle indicators of carrier status in two large families, using a robust endophenotyping method with good sensitivity and specificity to detect the BAP in two independent samples.…”
Section: Discussionmentioning
confidence: 99%
“…In other complex disorders, such as epilepsy, phenotypic characterisation of such families has proved powerful in gene discovery 18 , however this approach has received limited attention in ASD 1818 . In multiplex ASD families, the identification of family members with BAP traits, or endophenotypes, may serve as markers of carrier status 19,20 . In turn, this may facilitate gene identification 21 .…”
mentioning
confidence: 99%